Validation and field operationalization of one- and two-stage LAMP assay for diagnosis of COVID-19 in low-resourced health facilities in Ghana (VoLCOV) - Akorli, Jewelna (My University, 2024)
The rapid spread of the novel coronavirus disease, COVID-19, necessitates early detection of infected persons as part of strategies to identify and control community transmission. Testing for COVID-19 remain important especially for frontline workers, other high-risk groups and travellers. Although testing methods are available there remains avenues for improving and increasing the capacity to test and detect the virus.
Keywords: COVID-19; LAMP assay